The Genetic Polymorphisms of CYP3A4*1G and CYP3A5*3 in Javanese Indonesian Population: The Genetic Polymorphisms of CYP3A4*1G and CYP3A5*3 in Javanese Indonesian - Atmaja, Sarah; Ellsya Angeline Rawar; Ani Kristiyani; Dwi Aris Agung Nugrahaningsih; Ahmad Hamim Sadewa; Christine Patramurti (Journal of Tropical Life Science, 2024)
Polymorphisms of CYP3A4*1G and CYP3A5*3 affect the pharmacokinetic profile of various drugs, e.g., fentanyl, tacrolimus, diltiazem, simvastatin. Tetra-primer amplification refractory mutation system-polymerase chain (ARMS-PCR) is a simple and economical method for SNP determination. The polymorphisms in the CYP3A4*1G and CYP3A5*3 genes have not yet been examined using this method in Javanese Indonesian. Our aim was to determine the frequency of polymorphisms in the CYP3A4*1G and CYP3A5*3 genes in Indonesian Javanese using the ARMS-PCR method. Eighty-six patients at the Kalasan Community Health Centre in Yogyakarta, Indonesia, were chosen based on the inclusion criteria, which is Javanese ancestry. They gave their informed consent to blood collection by completing a form. Genetic variants were detected using Tetra-primer amplification refractory mutation system-polymerase chain (ARMS-PCR). The chi-square test was used to determine genotype deviations from Hardy-Weinberg equilibrium, with a significant threshold of 0.05. For homozygous wild types, CYP3A4 *1/*1 dominated overall among study participants (73.35%), whereas for CYP3A5*3/*3, homozygous mutants were more prevalent (83.72%). Hardy-Weinberg equilibrium is consistent with genotype frequencies (p > 0.005). One participant carried a homozygous mutation for both CYP3A4*1G and CYP3A5*3, while the other 49 subjects were heterozygous for CYP3A4*1G and homozygous mutant for CYP3A5*3, which is the highest number of SNP combinations. The findings of the current investigation demonstrate that the population has the highest proportion of homozygous CYP3A4*1G wild-types (CYP3A4*1/*1) and homozygous mutants for CYP3A5*3 (CYP3A5*3/*3)